2013
DOI: 10.31285/agro.17.518
|View full text |Cite
|
Sign up to set email alerts
|

Aumento en la producción de semillas de soja (Glycine max) empleando abejas melíferas (Apis mellifera)

Abstract: En Uruguay el incremento sostenido de los cultivos de soja (Glycine max) en los últimos años ha perjudicado a la industria apícola al desplazar a otros cultivos, por ejemplo las leguminosas forrajeras. Aunque la soja es una especie autógama, algunos estudios señalan que la producción de semillas puede incrementarse con insectos polinizadores, especialmente con abejas melíferas (Apis mellifera). El objetivo de este estudio fue determinar si las abejas melíferas y otros insectos incrementan la producción de semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
1
10
1
Order By: Relevance
“…However, more recent studies have shown that honey bees frequently forage in soybean fields, and cross-pollination by pollinators contributes additional benefits to soybean fruiting. Soybean yield is positively correlated with honey bee visitation, with yield increases ranging from 5.7% to 81% across studies, likely due to differences in experimental methods, soybean varieties, and variables such as time and location ( Jaycox 1970 , Erickson 1975a , Juliano 1976 , Erickson et al 1978 , Kettle and Taylor 1979 , Issa et al 1984 , Vila et al 1992 , Santos et al 2013 , Chiari et al 2005a , Toledo et al 2011 , Milfont et al 2013 , Monasterolo et al 2015 , Blettler et al 2018 , Esquivel et al 2021 , Levenson et al 2022 ). Chiari et al (2005a) demonstrated that pollination by honey bees and pollination by wild pollinators both increased soybean yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recent studies have shown that honey bees frequently forage in soybean fields, and cross-pollination by pollinators contributes additional benefits to soybean fruiting. Soybean yield is positively correlated with honey bee visitation, with yield increases ranging from 5.7% to 81% across studies, likely due to differences in experimental methods, soybean varieties, and variables such as time and location ( Jaycox 1970 , Erickson 1975a , Juliano 1976 , Erickson et al 1978 , Kettle and Taylor 1979 , Issa et al 1984 , Vila et al 1992 , Santos et al 2013 , Chiari et al 2005a , Toledo et al 2011 , Milfont et al 2013 , Monasterolo et al 2015 , Blettler et al 2018 , Esquivel et al 2021 , Levenson et al 2022 ). Chiari et al (2005a) demonstrated that pollination by honey bees and pollination by wild pollinators both increased soybean yield.…”
Section: Introductionmentioning
confidence: 99%
“…Sugar concentrations above 25% and low rates of cleistogamy are generally most attractive to honey bees ( Erickson 1975b ), whereas flower color has little impact on honey bee foraging ( Jaycox 1970 , Mason 1979 , Severson and Erickson 1984 , Chiang and Kiang 1987 ). Attractiveness also changes over time, with most studies observing peak honey bee activity in soybeans around midday ( Jaycox 1970 , Issa et al 1984 , Santos et al 2013 , Chiari et al 2005a , Toledo et al 2011 , BeaudelaineKengni et al 2015 , Blettler et al 2016 ). This is likely due to changes in floral nectar quality and quantity throughout the day, with sugar concentration increasing and nectar volume decreasing as the day progresses ( Severson and Erickson 1984 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cross-pollination in non-cleistogamous soybean varieties is facilitated by insects (Erickson et al 1978;Rust et al 1980;Milfont et al 2013). Many insect groups have been observed visiting soybean flowers, including Hymenoptera, Diptera, Coleoptera and Thysanoptera (Rust et al 1980;Ray et al 2003;Zhao et al 2009;Santos et al 2013;Gill & O'Neal 2015;Levenson et al 2022). To date, managed bees including honey bees (Apis mellifera) and alfalfa leafcutting bees (Megachile rotundata) are the most commonly studied pollinators in the soybean agroecosystem, with more recent studies focusing on wild bees (Gill & O'Neal 2015;Levenson et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of soybean pollination research has largely been pollinator-focused, exploring bee community composition (Gill & O'Neal 2015;Wheelock & O'Neal 2016;Levenson et al 2022), landscape ecology (Santos et al 2013;Zelaya et al 2018;Huais et al 2020), or changes in reproductive output through field-based pollinator-exclusion (i.e., plants are bagged to prevent visitation from floral visitors) and/or pollinator-addition experiments (i.e., pollinators were added to caged enclosures of soybean plants) (Garibaldi et al 2021;Santone et al 2022). However, to our knowledge the reproductive system of soybeans has not been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%
“…In some landscapes, these crops may host a more diverse community of bees than farms growing a variety of fruits and vegetables (St. Clair et al, 2020). Additionally, the presence of both honey bees and wild bees in soybean (Chiari et al, 2005;Santos et al, 2013;Kengni et al, 2015;Blettler et al, 2017) and sunflower (DeGrandi-Hoffman and Chambers, 2006;National Research Council, 2007;Chambó et al, 2011;Bartual et al, 2018;Mallinger et al, 2019) can increase yields through pollination services, although these yield increases may be cultivar specific (Erickson, 1975a).…”
mentioning
confidence: 99%